The Influence of Innovation Capability, Digital Transformation, and Supply Chain Integration on Competitive Advantage in the Automotive Industry in Indonesia - Susanto, Fredy; Wibowo, Sundaru Guntur (International Journal of Business, Law, and Education, 2025)
This study examines the influence of innovation capability, digital transformation, and supply chain integration on competitive advantage in the Indonesian automotive industry. Using a quantitative design, data were collected from 150 respondents representing managers and decision-makers in automotive firms. Constructs were measured using a five-point Likert scale, and data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that all three factors significantly and positively affect competitive advantage, with innovation capability having the strongest impact, followed by digital transformation and supply chain integration. These findings highlight the need for an integrated strategy, combining internal innovation, digital readiness, and external collaboration, to sustain competitiveness in a dynamic and globalized market. The study contributes to the Resource-Based View, Dynamic Capabilities, and Relational View theories by demonstrating how organizational capabilities, technological adaptation, and supply chain collaboration jointly shape competitive advantage in emerging economies. Managerial implications suggest that firms should invest in innovation, accelerate digital adoption, and strengthen supply chain partnerships to ensure long-term performance.